Prevention and Reversal of Diabetes by All-Trans Retinoid Acid and Exendin-4 in NOD Mice - Jyuhn-Huarng Juang; Yang-Hau Van; Chien-Hung Kuo; Mei-Yin Lin; Ying-Hsiu Liu; Han-Ying Chang (International Journal of Endocrinology)
It has been shown that all-trans retinoid acid (ATRA) hinders the development of autoimmune diabetes by inducing immune tolerance status. Meanwhile, exendin-4 increases beta-cell function and mass. Thus, we hypothesized that ATRA and exendin-4 combination therapy would prevent and reverse autoimmune diabetes. NOD/scid mice were intravenously transferred with splenocytes isolated from 12-week-old female NOD mice. After adoptive transfer, mice were treated with vehicle, ATRA (0.5 mg/mouse intraperitoneally every other day), exendin-4 (3 μg/kg subcutaneously twice daily), or combination for 6 weeks. Compared with vehicle, ATRA (P=0.022) and ATRA plus exendin-4 (P=0.013) treatment delayed the onset of diabetes. The pancreatic insulin content in mice treated with ATRA (P=0.013) and exendin-4 (P<0.02) was significantly higher than that of control mice. All but one spontaneous diabetic NOD mouse treated with ATRA and/or exendin-4 remained persistent hyperglycemic. ATRA and/or exendin-4 treatment did not alter their blood glucose levels and survival. Our results indicate that, before the onset of autoimmune diabetes, ATRA and exendin-4 treatment alone preserves pancreatic beta cells; ATRA and ATRA plus exendin-4 treatment delays the onset of autoimmune diabetes. However, after the onset of autoimmune diabetes, ATRA and/or exendin-4 treatment is unable to reverse hyperglycemia or improve survival.